Infectious profiles in pediatric anti-N-methyl-d-aspartate receptor encephalitis - Sandweiss, Alexander J.; Erickson, Timothy A.; Jiang, Yike; Kannan, Varun; Yarimi, Jonathan M.; Levine, Jesse M.; Fisher, Kristen; Muscal, Eyal; Demmler-Harrison, Gail; Murray, Kristy O.; Ronca, Shannon E. (Journal of neuroimmunology, 2023)
Anti-N-methyl-d-aspartate receptor autoimmune encephalitis (NMDAR AE) is an antibody-mediated neurological disorder that may be caused by post-herpes simplex virus-1 meningoencephalitis (HSV ME) and ovarian teratomas, although most pediatric cases are idiopathic. We sought to evaluate if other infections precede NMDAR AE by conducting a single-center, retrospective, case-control study of 86 pediatric cases presenting to Texas Children's Hospital between 2006 and 2022. HSV ME (HSV-1 and HSV-2) was a significantly more common preceding infection in the experimental group compared to control patients with idiopathic intracranial hypertension, while there was no difference in remote HSV infection between the two groups. Recent Epstein-Barr virus infection was evident in 8/42 (19%) tested experimental patients in comparison to 1/25 (4%) tested control patients which provided evidence for a genuine measure of effect but was not statistically significant due to small sample size (p = 0.07). The other 25 infectious etiologies were not different among the two groups and not all variables were clinically indicated or obtained in every subject, highlighting the need for future standardized, multi-institutional studies on underlying infectious precursors of autoimmune encephalitis. •In addition to HSV- 1, HSV- 2 meningoencephalitis is a likely precipitant of anti-NMDAR encephalitis.•Other Herpesviridae like EBV may predispose to NMDAR AE greater than previously appreciated, requiring further study.•Frequently detected concomitant infections with NMDAR AE like common respiratory viruses are less likely triggers of NMDAR AE.